The Controlled Distribution of a Crop among Independent Markets - Waugh, Frederick V.; Burtis, Edgar L.; Wolf, A. F. (Quarterly Journal of Economics, 1936)
I. Importance of the problem, 1. — What marketing textbooks call "orderly distribution" not the principle to follow, 3. — Statistical price studies have done little to clarify the general principles involved, 5. — II. The principle of equalized marginal returns, 6. — III. Even or uneven sales from year to year, 9. — IV. Allocation of supplies between two independent markets, 13. — V. Allocation of supplies among several independent markets, 18. — VI. Discriminative marketing and the general welfare, 32. — VII. Conditions for maximum net returns, 37.